Association of the stilt bug Jalysus ossesae Henry (Hemiptera : Heteroptera : Berytidae) with myrmecophytic plants of the genus Maieta (Melastomataceae) in an upland forest area in central Amazon, Brazil - Osses, Francini; Martins, Eduardo G.; Romero, Gustavo Q. (Entomol Soc Washington, 2007)
Maieta guianensis Aubl. and M. poeppigii Mart. ex. Triana (Melastomataceae) are among the most common myrmecophytic plants in the Amazonian forest understory. These myrmecophytes are colonized exclusively by the ants Pheidole minutula Mayr or Crematogaster sp. and usually host two other arthropods, the spider Faiditus subflavus Exline and Levi and the recently described stilt bug Jalysus ossesae Henry. In this study, the association between J ossesae and the myrmecophytic plants M. guianensis and M. poeppigii in an upland forest area in central Amazon, Brazil, is described. The presence of the stilt bugs on M. guianensis and M. poeppigii and on plants around these myrmecophytes was recorded in five transects. The number and position of the stilt bugs on the leaf surface (upper or lower) and leaf type (with or without domatia) of these myrmecophytes, as well as their behavioral acts, were recorded. Jalysus ossesae was found only on the myrmecophytic plants M. guianensis and M. poeppigii. The stilt bug occurred at similar frequencies on M. guianensis and M. poeppigii, and the number of leaves significantly influenced the presence and number of stilt bugs on these myrmecophytes. Feeding, agonistic interaction between males, and mating were observed. Our data indicate that J. ossesae uses the myrmecophytes M. guinanensis and M. poeppigii as reproductive and foraging sites.
Keywords: Hemiptera; animal-plant interaction; host plants; Maieta guianensis; Maieta poeppigii; trichomes; ant-plants